A Period Analysis on Values Shaped by Culture: Turkish and Armenian Women’s Clothing - Artac, Berna Yıldırım; Koca, Emine (European Scientific Journal, ESJ, 2018)
Written works such as miniatures, engravings and travel books, which contain visuals related to the Ottoman State, are considered to be documents bearing witness to history and imparting information about the daily life of the Ottoman Empire. These documents contain visuals of the people living in the Ottoman State, imparting, among other information, clues on the characteristics of the clothes of the period. In the Ottoman state cultural interaction often overrode attempts to create boundaries in the forms of clothing belonging to distinct communities. The resulting similarities in clothing form the starting point of this study. Focusing on the examination of clothes belonging to Turkish and Armenian women who lived in the Ottoman Empire in the18th and 19th centuries, this study aims to determine the similarities and differences between the clothing cultures of the two communities. A total of 22 images reflecting the everyday clothing of Turkish and Armenian women were examined with the help of a clothing examination form repared by the researchers. The visuals were analyzed according to form and usage, design features were explained, and the similarities and differences between the women’s garments were interpreted.